Using evidence to end homelessness - Teixeira, Lígia; Cartwright, James (Policy Press, 2020)
Available open access under CC-BY-NC license. This book brings together the insights and experiences of a diverse group of of government leaders, academics and third sector practitioners to set out new evidence-based strategies and solutions to end homelessness for good.